2021
DOI: 10.1093/fqsafe/fyab027
|View full text |Cite
|
Sign up to set email alerts
|

Using Risk–Benefit Analysis to Control Salmonella in Chicken Meat

Abstract: We have created a risk-benefit analysis (RBA) model to assist in food safety decision-making by analyzing Salmonella control in Brazilian chicken meat. First, we described the issues in a risk profile and used a 5 × 5 matrix to rank the risks associated with Salmonella. We then classified the magnitude of benefits and costs of control measures using another matrix. Finally, we verified the beneficial effects of recommended control measures using Quantitative Microbiological Risk Assessment (QMRA). The RBA clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Scalding is a process where chicken carcasses are either immersed in hot water or sprayed with hot steam to open the feather follicles of the skin to facilitate the removal of feathers (Cox & Pavic, 2010). Scalding can be a point in processing at which enteropathogen cross‐contamination can occur (Seliwiorstow et al., 2016; Tondo & Gonçalves, 2021). In a recent study, a pre‐scald cloacal wash with lactic acid (5%) was found to significantly reduce Campylobacter on carcasses in a commercial processing plant by 0.66 log 10 CFU/cm 2 relative to untreated carcasses.…”
Section: Meat Bird (Broiler) Processingmentioning
confidence: 99%
“…Scalding is a process where chicken carcasses are either immersed in hot water or sprayed with hot steam to open the feather follicles of the skin to facilitate the removal of feathers (Cox & Pavic, 2010). Scalding can be a point in processing at which enteropathogen cross‐contamination can occur (Seliwiorstow et al., 2016; Tondo & Gonçalves, 2021). In a recent study, a pre‐scald cloacal wash with lactic acid (5%) was found to significantly reduce Campylobacter on carcasses in a commercial processing plant by 0.66 log 10 CFU/cm 2 relative to untreated carcasses.…”
Section: Meat Bird (Broiler) Processingmentioning
confidence: 99%